The Effect of Working Hours on Health - Maria Ines Berniell; Jan Bietenbeck (Institute of Labor Economics (IZA), 2017)
Does working time causally affect workers' health? We study this question in the context of a French reform which reduced the standard workweek from 39 to 35 hours, at constant earnings. Our empirical analysis exploits variation in the adoption of this shorter workweek across employers, which is mainly driven by institutional features of the reform and thus exogenous to workers' health. Difference-in-differences and lagged dependent variable regressions reveal a negative effect of working hours on self-reported health and positive effects on smoking and body mass index, though the latter is imprecisely estimated. Results are robust to accounting for endogenous job mobility and differ by workers' occupations.
Keywords: I10; I12; J22; 330; working hours; health; smoking; BMI